Computer Models of Meander Slow-wave System with Additional Shields - Metlevskis, E.; Martavicius, R. (Elektronika ir Elektrotechnika, 2012)
In microwave devices various types of slow-wave systems are used. Meander slow-wave systems are widely used as delay lines and deflection systems because pass-band of such systems starts at low frequencies. Wideband signals which propagate through the meander slow-wave system are distorted because of the phase delay time dispersion. In this paper possibilities of reducing a phase delay time dispersion and widening the pass-band of meander slow wave system are analyzed. Three new models of a meander slow-wave system with additional shields are presented. Models are designed and analyzed using Sonnet® software. For comparison of the models phase delay time dependence on frequency is calculated from S21 parameters. The impact on dispersion properties of meander slow-wave system of grounding point of additional shield is investigated. Ill. 6, bibl. 16 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.119.3.1365